2008
DOI: 10.1620/tjem.214.311
|View full text |Cite
|
Sign up to set email alerts
|

Species and Antimicrobial Resistance of Uropathogens Isolated from Patients with Urinary Catheter

Abstract: A large number of hospitalized patients have an indwelling urinary tract catheter (IUC) placed at some time during their hospital stay and may suffer from catheter-associated urinary tract infections, the leading cause of nosocomial infections. Here we investigated the prevalence of uropathogens associated with catheter-associated urinary tract infections and assessed the resistances of these pathogens to commonly prescribed antibiotics. In total, 2,997 urine samples were examined at a regional hospital in Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…However, in this study, members of the genus Klebsiella 35.7% were more commonly identified compared to E. coli 5.4%, an observation that has been documented in CAUTI elsewhere (Habte et al, 2009). Other researchers have also concluded that the frequency of isolation of E. coli as a causative agent of UTI is slowly declining and it is being replaced by other members of the enterobacteriaceae and enterococci (Ko et al, 2008;Teshager et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, members of the genus Klebsiella 35.7% were more commonly identified compared to E. coli 5.4%, an observation that has been documented in CAUTI elsewhere (Habte et al, 2009). Other researchers have also concluded that the frequency of isolation of E. coli as a causative agent of UTI is slowly declining and it is being replaced by other members of the enterobacteriaceae and enterococci (Ko et al, 2008;Teshager et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…14 They also found that patients with a urinary tract catheter had higher resistance rates (mean 51%) to cefazolin, TMP-SMX, ciprofloxacin, and gentamicin than patients without a urinary tract catheter for Enterobacteriaceae. 14 In 2009, the most common pathogen in nosocomial UTIs among 1992 patients admitted at National Taiwan University Hospital (NTUH) was Candida spp. (26.6%) followed by E. coli (18.8%), Enterococcus spp.…”
Section: Taiwanmentioning
confidence: 99%
“…[5][6][7] Catheterization results in a higher prevalence of resistant organisms, including Pseudomonas species and rare gram-negative organisms. 9 In our patient, computed tomography of the abdomen and pelvis showed thickening of the cecum and terminal ileum with inflammatory stranding in the adjacent peritoneal fat. A fistulous communication was noted between a loop of terminal ileum and the dome of the urinary bladder.…”
Section: A History Of Whichmentioning
confidence: 50%